1999
DOI: 10.1152/ajpgi.1999.277.5.g944
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 stimulation of endothelial nitric oxide synthase in the pathogenesis of hepatopulmonary syndrome

Abstract: Biliary cirrhosis in the rat triggers intrapulmonary vasodilatation and gas exchange abnormalities that characterize the hepatopulmonary syndrome. This vasodilatation correlates with increased levels of pulmonary microcirculatory endothelial nitric oxide synthase (eNOS) and hepatic and plasma endothelin-1 (ET-1). Prehepatic portal hypertension induced by portal vein ligation (PVL) does not cause similar changes, suggesting that ET-1 in cirrhosis may modulate pulmonary eNOS and vascular tone. We assessed whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 30 publications
7
65
0
1
Order By: Relevance
“…2 Few experimental and clinical evidences in HPS suggest that enhanced pulmonary production of nitric oxide (NO) plays a key role in the development of intrapulmonary vascular dilatations. [3][4][5][6][7][8][9][10] Morphologically, the striking feature in HPS is widespread dilatation and increased number of pulmonary capillaries in alveolar regions 11 that suggest a vasculogenic rather than a vasoactive pathobiological process. 12 Studies with NO inhibitors in HPS, however, have highlighted that active NO-dependent pulmonary vasodilatation may contribute to the persistence of gas exchange abnormalities.…”
Section: See Editorial On Page 912mentioning
confidence: 99%
“…2 Few experimental and clinical evidences in HPS suggest that enhanced pulmonary production of nitric oxide (NO) plays a key role in the development of intrapulmonary vascular dilatations. [3][4][5][6][7][8][9][10] Morphologically, the striking feature in HPS is widespread dilatation and increased number of pulmonary capillaries in alveolar regions 11 that suggest a vasculogenic rather than a vasoactive pathobiological process. 12 Studies with NO inhibitors in HPS, however, have highlighted that active NO-dependent pulmonary vasodilatation may contribute to the persistence of gas exchange abnormalities.…”
Section: See Editorial On Page 912mentioning
confidence: 99%
“…97 Excess N O production has been shown in experimental models of hepatic encephalopathy, a neuropsychiatric syndrome associated with cirrhosis and portosystemic shunting.98 In this case, the relevant isoform may be nNOS. Increases in nNOS mRNA, protein, and activity have been shown in experimental models of hepatic encepha10pathy.9~ Interestingly, the excess in N O production may contribute to encephalopathy through mechanisms of neurotransmission regulation or through alterations in cerebral perfusion.…”
Section: No and Regional Circulatory Bedsmentioning
confidence: 99%
“…Most recently, we have observed that delivery of a chronic low level ET-1 infusion to PVL animals triggers an increase in pulmonary eNOS levels, intrapulmonary vasodilatation, and gas exchange abnormalities indicative of HPS. 6 Together, these findings suggest that circulating ET-1 derived from the liver contributes to the development of experimental HPS.…”
mentioning
confidence: 86%
“…Most recently, we have observed that delivery of a chronic low level ET-1 infusion to PVL animals triggers an increase in pulmonary eNOS levels, intrapulmonary vasodilatation, and gas exchange abnormalities indicative of HPS. 6 Together, these findings suggest that circulating ET-1 derived from the liver contributes to the development of experimental HPS.However, whether biliary production and release of ET-1 is involved in the unique susceptibility of CBDL animals to HPS remains undefined. We hypothesized that biliary obstruction may result in the release of mediators, including ET-1, from the obstructed biliary tree that reach the systemic circulation via disruption of the canalicular paracellular barrier and influence the pulmonary vasculature.…”
mentioning
confidence: 90%
See 1 more Smart Citation